Micro climate analysis in plastic hood on raisingcrops curly lettuce(lactuca sativa var. Cripal) - Andika, I Kadek Ari; Setiyo, Yohanes; Sanjaya, I Gede Budi (Jurnal BETA (Biosistem dan Teknik Pertanian), 2026)
The purpose of this study were to (1) analyze the microclimate within the plastic hood different heights for the cultivation of curly lettuce plants and (2) know the height of the suitable plastic hood on the productivity of the curly lettuce plant. This research using completely randomized design, with four treatments and three replications: SP0 treatment without hood, SP1 treatment of plastic hood height 80 cm with a height of 45cm ventilation, SP2 treatment of plastic hood height 100 cm with a height of 45 cm ventilation, and SP3 treatment of plastic hood height 120 cm with height ventilation 45 cm. The result of this research on treatment of plastic hood height 120 cm obtain highest light intensity at 651.1 lux, got the highest temperature at 24.10C and treatment of plastic lid height 80 cm obtain highest relative humidity at 76.3%. The Treatment hood height plastic of 80 cm obtained the highest productivity of 5.6 g/plant